(untitled) (Bangladesh Journal of Zoology, 2019)
Nile tilapia (Oreochromisniloticus) of average 2.08 ± 0.06 to 2.14 ± 0.19 g fry nursed in nine-floating net-cages of 3 × 3 × 1.5 m in highstocking densitiesof 600, 800 and 1000 fry m–3 densities in triplicate. The fish were hand-fed a commercial tilapia floating feed at a rate of 5 to 30% of their body weight thrice daily. The final mean weight of tilapia ranged 15.13 ± 0.28 to 24.10 ± 0.35 g with the mean daily weight gain of 0.21 ± 0.11 to 0.38 ± 0.05 g/day. The low stocking density of 600 fry m–3 had significant higher mean weight, daily growth rate and specific growth rate than did the higher density treatment of 1000 fry m–3.The food conversion ratio were (1.46 to 2.30) significantly affected by stocking density (p<0.05). Moreover, the net profit (BDT 1262 ± 85 - 2152 ± 55) showeda significant difference with increasing stocking density (p < 0.05). The growth of nursing fry was found to be density dependent. However, survival rates were found high in all treatments and were not affected by density. But, higher gross yield was observed at the highest density. The results of this study has clearly demonstrated that the higher density (800and1000 fry m–3) could be more profitable for tilapia cages than the lower density (600fry m–3) in terms of cost effectiveness and to meet the demand for large scale fish production. Bangladesh J. Zool. 47(1): 149-158, 2019